Life-History Strategy, Food Choice, and Caloric Consumption - Laran, Juliano; Salerno, Anthony (Psychological Science, 2013)
Do people's perceptions that they live in a harsh environment influence their food choices? Drawing on life-history theory, we propose that cues indicating that the current environment is harsh (e.g., news about an economic crisis, the sight of people facing adversity in life) lead people to perceive that resources in the world are scarce. As a consequence, people seek and consume more filling and high-calorie foods, which they believe will sustain them for longer periods of time. Although perceptions of harshness can promote unhealthy eating, we show how this effect can be attenuated and redirected to promote healthier food choices.